"Anjaneya" health drink: re-positioning dilemma. Issue 4 (2nd November 2018) - Sharma, Aasha Jayant; Sonwaney, Vandana Prashant
Abstract : Learning outcomes: The students will get a hands on research techniques like mental mapping, laddering and means end chain (MEC) model for value proposition and survey techniques. Case overview/synopsis: Market Research has always acted as one of the major driving force behind the successful launch of any product in any market. There are several evidences of how market research and thorough understanding of the consumers in and out has lead companies reach new peaks and acquire market share. This case deals with a company called Eco-Remedies, based in Nashik, India, which is in the business of providing eco-solutions to different health ailments and also general purpose health supplements like health drinks. The major concentration is on the product called "AnjaNeya-The Graviola fruit drink" from Eco-Remedies, where in different research techniques were used to gather information so that appropriate strategies could be implemented in order to increase the market share of the product and create a strong position in the minds of the customers. The case deals with gathering consumer insights and then developing appropriate positioning strategies for Eco remedies based on consumer value proposition using the MEC theory, mental mapping, blind tests and general consumer survey. Complexity academic level: The study is applicable to Masters level Marketing Management and Marketing Research Studies. Supplementary materials: Teaching Notes are available for educators only. Please contact your library to gain login details or email support@emeraldinsight.com to request teaching notes. Subject Code: Marketing.